Evaluación de la capacidad infectiva de un inoculante y de métodos de inoculación - Fernandez, Leticia Andrea (2004)
The nodule-appearance period was studied by means of a plant infection technique usinginoculants that had been stored at 5, 20 and 30°C during 16 and 31 days. In addition, two soybeaninoculation methods were compared via experiments in the growth chamber: seed-applied inoculationand soil-applied inoculation. The aplication of a liquid inoculant directly on soil surface was donethe day of the sewing, and 5, 11 and 20 days after planting at diferent distances from the seed (0 cm,1 cm and 2 cm). Results indicated that inoculated plants with an inoculant stored at high temperature(30ºC) during 31 days delayed soybean nodulation. An increase in both the nodule weight andnumber was observed when inoculation was carried out on the soil surface.